Evidence-based health promotion in nursing homes: A pilot intervention to improve oral health. Issue 5 (3rd May 2016) - Cadet, Tamara J.; Berrett-Abebe, Julie; Burke, Shanna L.; Bakk, Louanne; Kalenderian, Elsbeth; Maramaldi, Peter
ABSTRACT: Nursing home residents over the age of 65 years are at high risk for poor oral health and related complications such as pneumonia and adverse diabetes outcomes. A preliminary study found that Massachusetts' nursing homes generally lack the training and resources needed to provide adequate oral health care to residents. In this study, an intervention targeting Certified Nurses' Aides (CNAs) was developed and tested. We hypothesized that following the training, CNAs would have increased knowledge and self-efficacy toward providing oral health care to the residents in their charge. This pilot study used a one-group pretest-posttest design to test the effectiveness of a psycho-educational training intervention. Utilizing the constructs of knowledge and self-efficacy from the Theory of Planned Behavior and the Social Cognitive Theory, we framed the content of a training intervention and administered a 21-item instrument. The survey was distributed to the CNA staff of a single midsize nursing home immediately prior to and after the intervention. The 1-hour training intervention was empirically supported by formative data and delivered by dental faculty researchers. Findings indicate increases in two areas of oral health knowledge: toothbrush position and frequency of brushing. Self-efficacy, however, did not significantly change. Although the results marginally supported our hypothesis, this pilot study demonstrates the feasibility of delivering interventions to CNAs who have direct responsibility for promoting the oral health of long-term care facility residents.